Application of Sound Insulation Technology in Floating Floor. Issue 1 (August 2020) - Fang, Wenmin; Hong, Xiaowei; Lai, Linfeng
Abstract: In this paper, the sound insulation performance of the floating floor is studied from the perspective of its structural application. The field test shows that the sound insulation improvement value of the dry laying method is higher than that of the wet sticking method. At the same time, the influence of the construction technology of the floating floor on the load and net height of the building structure is summarized and compared. Finally, the weighted standardized impact sound pressure level of the field test is higher than the normalized impact sound pressure level measured in the laboratory This universal phenomenon is analyzed. This paper puts forward the construction technology of dry laying method of floating floor with sound insulation mat, which can provide reference for the construction of sound insulation mat laying on reinforced concrete floor and the design of building structure.